2021
DOI: 10.1111/jgh.15474
|View full text |Cite
|
Sign up to set email alerts
|

Exercise physiology in cirrhosis and the potential benefits of exercise interventions: A review

Abstract: Reduction in muscle mass is a highly prevalent phenomenon in cirrhosis and is now well-documented to be associated with significant morbidity and mortality. Research into muscle loss in cirrhosis remains limited by an ongoing poor understanding of its relationship with muscle function, physical activity, and aerobic capacity. Alterations in exercise physiology have been documented in studies of individuals with cirrhosis that provide important information on physical function that is not captured by simple qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…A similar observation was reported in a study by Román et al in 2016 [ 32 ]. Other studies found promising results regarding quality of life, physical function, and physical capacity by improving physical activity in cirrhotic patients [ 33 ]. Patients receiving HMB supplementation together with general lifestyle prescriptions achieved, in addition, a significant improvement in muscle performance.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was reported in a study by Román et al in 2016 [ 32 ]. Other studies found promising results regarding quality of life, physical function, and physical capacity by improving physical activity in cirrhotic patients [ 33 ]. Patients receiving HMB supplementation together with general lifestyle prescriptions achieved, in addition, a significant improvement in muscle performance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review showed that several studies investigated the effect of exercise on quality of life using different instruments with positive results (35) . We observed that the HG achieved lower scores in relation to the FG in all domains.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment strategies for sarcopenia in liver cirrhosis, which are mainly in investigational stages, include hormone replacement, antibiotics and gut microbiota manipulation, ammonia reduction, myostatin antagonists, nutritional supplementation such as branched-chain amino acids (BCAA) and L-carnitine supplements, and treatment of portal hypertension [29]. Although nutritional interventions and exercise, particularly resistance training, have been considered the main strategies to prevent sarcopenia in various populations [17,21,30].…”
Section: Impact Of Malnutrition In Patients With Liver Cirrhosismentioning
confidence: 99%